Cooperative Surface Passivation and Hierarchical Structuring of Zeolite Beta Catalysts. (29th August 2022) - Han, Sungmin; Linares, Noemi; Terlier, Tanguy; Hoke, Jeffrey B.; García Martínez, Javier; Li, Yuejin; Rimer, Jeffrey D.
Abstract: We report a method to prepare core–shell zeolite beta (*BEA) with an aluminous core and an epitaxial Si‐rich shell. This method capitalizes on the inherent defects in *BEA crystals to simultaneously passivate acid sites on external surfaces and increase intracrystalline mesoporosity through facile post‐hydrothermal synthesis modification in alkaline media. This process creates more hydrophobic materials by reducing silanol defects and enriching the shell in silica via a combination of dealumination and the relocation of silica from the core to the shell during intracrystalline mesopore formation. The catalytic consequences of *BEA core–shells relative to conventional analogues were tested using the biomass conversion of levulinic acid and n ‐butanol to n ‐butyl levulinate as a benchmark reaction. Our findings reveal that siliceous shells and intracrystalline mesopores synergistically enhance the performance of *BEA catalysts. Abstract : The synthesis of core–shell zeolite beta (*BEA) produces a zeolite with an epitaxially grown Si‐rich shell on the exterior rim, which passivates the surface reactivity. It is also possible to enhance intracrystalline mesoporosity via secondary hydrothermal treatment by taking advantage of intrinsic silanol defects in *BEA.